Ten years review of Hepatocellular carcinoma In Hospital Universiti Sains Malaysia (1996-2005) - Aman, Ab. Latif (2007)
Hepatocellular carcinoma (HCe) is the most co=on primary malignancy of the liver and one of the most co=on causes of death from cancer. Local literature on HCC are rather scare and hence the need for a study of this nature. One hundred eight (108) patients were diagnosed ofHCC in a period often years from 1996 to 2005 at Hospital Universiti Sains Malaysia were studied to determine the pattern of the disease and to highlight the clinical presentation, co=on risk factors, mode of investigation, stage at presentation, modalities offered for treatment and the survival rate. The mean age of occurrence was 57.9 ± 11 .5 years. Male to female ratio was 3: 1 and predominantly affecting the Malays (83.3%). Hepatitis B was the main risk factor for HCC in 68(63%), where as Hepatitis C was positive in 9(8.3%). The clinical presentations included abdominal discomfort in 98(90.7%), abdominal pain in 55(50.9%), abdominal distension in 68(62.7%), loss of weight in 62(57.4%), stigmata of chronicliver disease in 51(47.2%) and jaundice in 52(48.1 %) patients. Solitary type of lesion in 30(72.2%) and multiple type in 78(72.2%) patients. The largest diameter varied from<5cmin33(30.5%), 5-lOcmin 66(6 l.l%)to >10cm in 9(8.3%) patients. Portal vein thrombosis presented in 59(54.6%) and 27(25%) already with distant metastases. Severity of liver impairement as assesed by Child Pugh Classification, 39(36.1%) presented with Child's A, 40(37%) with Child's B and 29(26.9%) with Child's C. Tumor grading by TNM staging showed patients presented with unresectable tumor due to locally advanced stage were 66(61.1%) and advanced stage 32(29.6%). Where as 10(9.3%) of patients at resectable stage of tumor. Most patients 77(71.3%) given supportive treatment. Anti tumour agent only given to 4(3.7%) patients and 1(0.9%) patient underwent emergency surgical resection. Death mainly related to HCC, account for 82.4%( 89). Overall mean survival was 5.2 months. Statistically showed that sex, location of tumour, Child Pugh Classification, Okuda staging and mode of treatment were related with the survival in this study. In conclusion, most hepatocellular Carcinoma cases admitted to HUSM presented in advanced stage put them unsuitable for surgical resection or anti tumour treatments modalities. More effort should be taken to detect early stage of HCC so that curative treatment can be aimed to prolong the survival rate.